The Mediation Process at the Soreang Religious Court Becomes a Means of Reconciliation in Divorce Cases in Soreang, Bandung Regency Based on Supreme Court Regulation Number 1 of 2016 - Ahmad Solehudin; Saim Aksinudin (Journal of Law, Politic and Humanities, 2024)
Divorce is an event that often involves various conflicts and complex issues, both from a legal and social perspective. Religious Courts have a key role in handling divorce cases and mediation has been one of the approaches applied to seek amicable solutions in these cases. This study aims to find out how the Soreang Religious Court handles divorce cases in Bandung Regency in accordance with Supreme Court Regulation No. 1 of 2016. This research adopted a qualitative method. The process of collecting information through literature study. Once the data was collected, analysis was conducted in three stages: data reduction, data presentation, and conclusion drawing. The research shows that the Soreang Religious Court uses mediation as the final step to resolve divorce cases in Bandung Regency. Most divorce cases have been successfully resolved through this mediation approach. In addition, there are several factors that influence the success of mediation at the Soreang Religious Court, such as the willingness of both parties to follow the mediation process, the mediator's ability to understand and resolve the problems faced by the parties, and also the support of various related parties such as judges, clerks, and other parties involved in the mediation process.